Addressing climate change and conflict in development cooperation: Experiences from natural resource management - Mikkel Funder; Signe Marie Cold-Ravnkilde; Ida Peters Ginsborg (Danish Institute for International Studies (DIIS), 2012)
The report presents the main findings of a desk study of experiences with conflict prevention and resolution in natural resource management, and how these can be applied in development cooperation in relation to climate change. The report briefly discusses the link between climate change and conflict, including the need to see climate change as a conflict multiplier rather than as a major direct cause of conflict in itself. It then goes on to review approaches and lessons learnt from conflict prevention and resolution in natural resource management at the local, national and transboundary levels respectively. On this basis, the report provides recommendations on how development cooperation can address the potential conflict multiplier effects of climate change, including guiding principles and key entry points for support. The latter include (i) enhancing so-called structural conflict prevention measures, (ii) supporting institutional mechanisms for managing and resolving conflict, and (iii) 'conflict proofing' policies and development interventions.
Keywords: 300